Soil charcoal as long-term pyrogenic carbon storage in Amazonian seasonal forests - Turcios, Maryory M.; Jaramillo, Margarita M.A.; Vale, José Frutuoso do; Fearnside, Philip Martin; Barbosa, Reinaldo Imbrozio (Global Change Biology, 2016)
Forest fires (paleo + modern) have caused charcoal particles to accumulate in the soil vertical profile in Amazonia. This forest compartment is a long-term carbon reservoir with an important role in global carbon balance. Estimates of stocks remain uncertain in forests that have not been altered by deforestation but that have been impacted by understory fires and selective logging. We estimated the stock of pyrogenic carbon derived from charcoal accumulated in the soil profile of seasonal forest fragments impacted by fire and selective logging in the northern portion of Brazilian Amazonia. Sixty-nine soil cores to 1-m depth were collected in 12 forest fragments of different sizes. Charcoal stocks averaged 3.45 ± 2.17 Mg ha-1 (2.24 ± 1.41 Mg C ha-1). Pyrogenic carbon was not directly related to the size of the forest fragments. This carbon is equivalent to 1.40% (0.25% to 4.04%) of the carbon stocked in aboveground live tree biomass in these fragments. The vertical distribution of pyrogenic carbon indicates an exponential model, where the 0-30 cm depth range has 60% of the total stored. The total area of Brazil's Amazonian seasonal forests and ecotones not altered by deforestation implies 65-286 Tg of pyrogenic carbon accumulated along the soil vertical profile. This is 1.2-2.3 times the total amount of residual pyrogenic carbon formed by biomass burning worldwide in 1 year. Our analysis suggests that the accumulated charcoal in the soil vertical profile in Amazonian forests is a substantial pyrogenic carbon pool that needs to be considered in global carbon models. © 2016 John Wiley & Sons Ltd.
Keywords: Carbon Cycle; Carbon Sequestration; Charcoal; Forest Fires; Forest Soil; Soil Profile; Vertical Distribution; Amazonia; Charcoal; Soil; Carbon Cycle; Chemistry; Environmental Protection; Fire; Forest; Forestry; Procedures; Soil; Tree; Carbon Cycle; Charcoal; Conservation Of Natural Resources; Fires; Forestry; Forests; Soil; Trees